Kekudusan Seorang Imam Menurut Yohanes Krisostomus - hisikia gulo; Meiman Gulo (Institut Agama Kristen Negeri Manado, 2022)
The holiness of a priest is the main thing that God wants as a person who is given a mandate by God and guides believers to the maturity of faith in Jesus Christ. The purpose of this research is to contribute to each church priest to continue to carry out their duties and responsibilities as a servant and a person who trusts God and maintains a holistic life in ministry. Because the holiness of a person has a major influence on the maturity of the church's faith. The research method is literature review with interaction with texts in the Bible. The results of the analysis show that the holiness of a priest has a major impact on the spiritual growth of believers.